2013
DOI: 10.1177/1359105313483644
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic reactions to an earthquake: Multidimensional scaling profile analysis of adolescent survivors

Abstract: The current study examined the prototypical profiles of posttraumatic stress reactions among a sample of 282 adolescent survivors of the 2008 Wenchuan earthquake in China. Based on a dimensional perspective, the results of profile analysis via multidimensional scaling (PAMS) model revealed a two-dimensional solution corresponding to four profiles: intrusion, avoidance/arousal, partial avoidance, and hyperarousal. These profiles of posttraumatic stress symptoms equally manifested across gender. In addition, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Thus, perceived safety, which is a cognitive belief about getting away from fear and anxiety, becomes more evident in the process of approach-symptoms in the fifth week after disaster; that is, given the more pathological nature of reexperiencing and hyperarousal, perceived safety may play a more prominent moderating role in the process of approach-symptoms. In addition, this finding was consistent with previous studies that approach-symptoms were more likely related to other psychological distresses, such as anxiety and somatization (Ding & Xia, 2013), and lower perceived safety was related with higher reexperiencing and hyperarousal but not the avoidance and numbing (Fullerton et al, 2006). When it comes to the mechanism underlying the relationship between social support and avoidance and numbing, other factors such as individuals’ coping style and time duration may be worked in this process.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, perceived safety, which is a cognitive belief about getting away from fear and anxiety, becomes more evident in the process of approach-symptoms in the fifth week after disaster; that is, given the more pathological nature of reexperiencing and hyperarousal, perceived safety may play a more prominent moderating role in the process of approach-symptoms. In addition, this finding was consistent with previous studies that approach-symptoms were more likely related to other psychological distresses, such as anxiety and somatization (Ding & Xia, 2013), and lower perceived safety was related with higher reexperiencing and hyperarousal but not the avoidance and numbing (Fullerton et al, 2006). When it comes to the mechanism underlying the relationship between social support and avoidance and numbing, other factors such as individuals’ coping style and time duration may be worked in this process.…”
Section: Discussionsupporting
confidence: 91%
“…In doing so, however, we did not suggest that these survivors suffered from PTSD. Rather we tended to believe that the survivors were more likely to suffer some PTSD symptoms, as suggested by Ding and Xia (2013). Although some of the survivors may develop full PTSD, this is not typical for most survivors (Ding & Xia, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…PSTD is a psychological disorder which can occur after people went through a traumatic experience such as earthquakes, hurricanes and SARS (Ding and Xia, 2014; Gonzalez et al, 2019; Mak et al, 2010). Its basic feature is the characteristic symptoms result from the exposure to a traumatic experience, or a personal tragic life event, or witness events involving death, injury or threat to the physical integrity of others (Lin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggested that traumatized individuals might show some psychological problems such as posttraumatic stress disorder (PTSD), depression, and anxiety following natural disasters (Ding and Xia, 2014; Gan et al, 2013; Liang, 2017). Particularly, PTSD was considered as one of the common negative psychological outcomes following natural disasters such as floods (e.g.…”
Section: Introductionmentioning
confidence: 99%